Intellectual Radicalism after 1989 Crisis and Re-orientation in the British and the American Left - Berg, Sebastian (Edition Politik, 2017)
Left-wing intellectuals in Britain and the US had long repudiated the Soviet regime. Why was the collapse of the Eastern Bloc experienced as a shock that destabilised their identities and political allegiances then? What happened to a collective project that had started out to formulate a socialist vision different from both really existing socialism and social democracy? This study endeavours to answer both questions, focusing on generational networks rather than individuals and investigating political academic journals after 1989 to paint the picture of a Left deeply troubled by the triumph of a capitalism unfettered by any counter-force.